2004
DOI: 10.1111/j.1399-5618.2004.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neuronal activation in patients with bipolar disorder during performance of a working memory task

Abstract: Our findings suggest that decreased working memory performance in bipolar patients reflects specific neurofunctional deficits. These deficits may represent primary areas of neuropathology or be secondary to neuropathology elsewhere in the working memory network. Continued research utilizing other imaging modalities may further clarify the underlying neuropathology involved in these cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
148
1
12

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(183 citation statements)
references
References 64 publications
19
148
1
12
Order By: Relevance
“…Similarly, functional neuroimaging (SPECT, PET, FMRI) has consistently identified prefrontal and temporal brain activation during working memory performance (41,42,(67)(68)(69)(70)(71)(72). This study probed working memory via the N-Back paradigm adapted for FMRI and demonstrated that the same cortical structures were involved.…”
Section: Fmri In Childhood-onset Sle 4159mentioning
confidence: 80%
“…Similarly, functional neuroimaging (SPECT, PET, FMRI) has consistently identified prefrontal and temporal brain activation during working memory performance (41,42,(67)(68)(69)(70)(71)(72). This study probed working memory via the N-Back paradigm adapted for FMRI and demonstrated that the same cortical structures were involved.…”
Section: Fmri In Childhood-onset Sle 4159mentioning
confidence: 80%
“…In order to control for multiple comparisons and protect against type I error a clustering technique was employed. Specifically, a minimum cluster size of 15 with a significance threshold of po0.05 was used to identify activation, as previously suggested (Adler et al, 2001a(Adler et al, , 2004. Functional maps were coregistered to a structural template of averaged T1-weighted MDEFT structural images to aid interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Binary masking was applied to each image to remove pixels outside the brain. Linear and quadratic drift components in the temporal baseline of each pixel were removed using a quadratic drift correction algorithm (Adler et al, 2001a(Adler et al, , b, 2000(Adler et al, , 2004. Subjects' head movements were minimized by instructing them to remain still and by packing foam padding around their heads.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…3 However, some recent investigations and the present results provide evidence of hyperactivation of prefrontal cortex or 'hyperfrontality' during working memory tasks in patients with mood disorder. 25,47 The association between task performance and frontal activation is not consistent. In some studies showing hypofrontality, the patients' cognitive or working memory performance was much poorer than that of the controls 28,30,48 and in the other studies the patients' performance was not significantly different from that of the controls.…”
Section: Working Memory In Depression K Matsuo Et Almentioning
confidence: 97%
“…In some studies showing hypofrontality, the patients' cognitive or working memory performance was much poorer than that of the controls 28,30,48 and in the other studies the patients' performance was not significantly different from that of the controls. 26,49 One study demonstrating hyperfrontality showed poor performance in the patients on the n-back task (n > 0) compared to controls, 47 and the other showed no difference in cognitive task performance between the patients and the healthy controls. 25 The MDD patients in our study showed this pattern of hyperfrontality without impaired cognitive task performance.…”
Section: Working Memory In Depression K Matsuo Et Almentioning
confidence: 99%